KUASA MEDIA ATAS MASTURBASI: STUDI DISKURSUS YOUTUBE CLARIN HAYES DAN LAMPU ISLAM - Mawlana, Akbar; Ulumuddin, Naufalul Ihya’ (Paradigma: Jurnal Kajian Budaya, 2022)
Various productions of knowledge about masturbation are channeled through the media. The production of knowledge disseminated through technology presents ambivalent conditions that make individual consciousness never complete. However, various studies on masturbation have not touched the media aspect. Therefore, the purpose of this research is to examine the power of the media on masturbation in producing social body discipline. Foucault’s concept of discourse becomes a theoretical knife. Foucault’s discourse orientation leads to an analysis of the power of knowledge on the discipline of social action. The research method is qualitative. The media used are Youtube Clarin Hayes and Lampu Islam. The results of the study show that the media is never neutral, because it is intertwined with the politics of knowledge. It affects the social reality of society in creating sex ideologies and technologies that go beyond the biological body.